On sluggish output and exchange rate dynamics once again - Natividad-Carlos, Fidelina B. (1997)
This paper examines a model of exchange rate dynamics which incorporates sluggish output adjustment into the Dornbusch variable output model. In this model where both the price level and output cannot jump, the interest rate must decline in response to a monetary expansion so as to maintain money market equilibrium. As the interest rate declines, because of uncovered interest rate parity, there must be an expectation of a subsequent appreciation. However, the exchange rate need not necessarily overshoot initially and yet an expectation of a subsequent appeciation is created because expectations depend not only on the initial exchange rate deviation, as in the Dornbusch model, but also on the initial price deviation and these two deviations are now different sources of information for rational speculators. Furthermore, by explicitly deriving the time paths of the exchange rate and other variables, it is shown that indeed, consistent with perfect foresight, whatever is the initial exchange rate response, such is subsequently followed by actual appreciation.
Keywords: Foreign exchange rates; Interest rates; Demand (Economic theory)